Um estudo sociológico sobre as compreensões de felicidade dos docentes do IFFar, Campus Santo Augusto - RS - Corrêa, Ricardo (2023)
This research seeks, through a genealogy of happiness in the West, to explain the reasons why the theme of happiness has been valued since Greek philosophy and has adapted, in certain periods, to ideology and worldviews, or has been almost forgotten in other periods (centuries) in Eurocentric intellectual history. When the theme of happiness reappears in modernity, little by little, it moves from the philosophical and ethical spheres to enter the scientific field and be the object of scientific research. To confirm our thesis, we analyzed the last two World Happiness Reports (2022 – 2023) and, also, as a complementary work, we sought to research, in a scientific way, the understandings of happiness of the teachers of IFFar – Campus Santo Augusto/RS. Therefore, this scientific research, together with the intention of doing scientific research on the topic of happiness, finds a meta-explanation from the genealogy of happiness.